A Comparison of Markov Chain Methods for Reliability Estimation. Issue 1 (15th March 2018) - Proppe, Carsten
Abstract: Two Markov chain Monte Carlo simulation methods for reliability estimation, subset simulation and the moving particles algorithm, are compared based on theoretical arguments and test cases. The differences in the efficiency between both algorithms are rather small. They seem to be well suited for off‐the‐shelf reliability estimations, but with a different setting for the most important parameters (proposal density and initial sample size). (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)